Self-Empowerment, Affirmation And Relaxation Training Against Stress Levels And Cortisol Levels In Pregnant Women: Systematic Literature Review - F, Hasriyanti Romadhoni; Supriyana, Supriyana; Runjati, Runjati (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The incidence of stress in pregnancy in the world is 14-54%. The incidence of stress in pregnant women in Indonesia reaches 55.6%. interventions can potentially reduce stress and the hormone cortisol during pregnancy. To analyze self-empowerment, affirmation, and relaxation training which have the potential to reduce stress and cortical hormone scores in pregnant women based on literature studies that have been conducted. Systematic Literature Review research using the PRISMA method. The period studied is from 2016-2020. The potential to reduce levels of stress and the hormone cortisol is more effective using the Self-empowerment method during pregnancy, which means that it can reduce stress during pregnancy and the impact it will have on the mother and the fetus. It was concluded that the intervention (self-empowerment, affirmation, and relaxation) was proven to reduce stress scores and the hormone cortisol in pregnant women.